Role of Multimodal Imaging in Patients With Suspected Infections After the Bentall Procedure - Sollini, Martina; Bartoli, Francesco; Boni, Roberto; Zanca, Roberta; Colli, Andrea; Levantino, Maurizio; Menichetti, Francesco; Ferrari, Mauro; Berchiolli, Raffaella; Lazzeri, Elena; Erba, Paola A. (Frontiers in Cardiovascular Medicine, 2021)
Purpose: This study aimed to assess the diagnostic performances of WBC SPECT/CT and [18F]FDG PET/CT in patients with suspected infection after a Bentall procedure, proposing new specific diagnostic criteria for the diagnosis. Methods: Between January 2009 and December 2019 we selected within a cardiovascular infections registry, 76 patients (23 women and 56 men, median 66 years, range 29-83 years) surgically treated with replacement of the aortic valve and ascending aorta according to the Bentall procedure who performed molecular imaging for a suspected infection. We analyzed 98 scans including 49 99mTc-WBC and 49 [18F]FDG-PET/CT. Twenty-two patients with very early/early suspected infection (<3 months after surgery) were studied with both procedures. Positive imaging was classified according to the anatomical site of increased uptake: to the aortic valve (AV), to both aortic valve and aortic tube graft (AVTG) or to the TG, to surrounding tissue, and/or to extracardiac sites (embolic events or other sites of concomitant infection). Standard clinical workup included in all patients echocardiography/CT, blood culture, and Duke criteria. Pre-test probability and positive/negative likelihood ratio were calculated. Sensitivity and specificity of 99mTc-HMPAO-WBC SPECT/CT and [18F]FDG PET/CT imaging were calculated based on the final microbiological (n=35) or clinical diagnosis (n=41). 99mTc-HMPAO-WBC scintigraphy and [18F]FDG PET/CT findings were compared with 95% confidence intervals using the McNemar test to those of echocardiography/CT, blood culture, and Duke criteria. Results: WBC sensitivity was 86%, specificity 92%, and accuracy 88%, with a slightly higher sensitivity for TGI as compared to isolated AV and combined AVTG. [18F]FDG PET/CT overall sensitivity, specificity, and accuracy were 97%, 73%, and 90%, respectively. In the 22 patients with suspected very early and early post-surgical infections, the two imaging modalities were concordant in 17 cases (10 TP and 7 TN). [18F]FDG PET/CT presented a higher sensitivity than WBC scan. WBC scan correctly classified as negative the 3 FP PET/CT findings. Conclusions: Our findings supported the use of 99mTc-HMPAO-WBC SPECT/CT and [18F]FDG PET/CT in patients with suspicion infection after Bentall procedure early in the course of the disease onset to confirm the diagnosis and provide a comprehensive assessment of disease burden trough the proposed criteria.